An Ongoing Tidal Capture in the Large Magellanic Cloud: The Low-mass Star Cluster KMK 88-10 Captured by the Massive Globular Cluster NGC 1835? - Camilla Giusti; Mario Cadelano; Francesco R. Ferraro; Barbara Lanzoni; Silvia Leanza; Cristina Pallanca; Enrico Vesperini; Emanuele Dalessandro; Alessio Mucciarelli (The Astrophysical Journal, 2023)
In the context of a project aimed at characterizing the dynamical evolution of old globular clusters in the Large Magellanic Cloud, we have secured deep HST/WFC3 images of the massive cluster NGC 1835. In the field of view of the acquired images, at a projected angular separation of approximately 2′ from the cluster, we detected the small stellar system KMK 88-10. The observations provided the deepest color–magnitude diagram ever obtained for this cluster, revealing that it hosts a young stellar population with an age of 600–1000 Myr. The cluster surface brightness profile is nicely reproduced by a King model with a core radius r _c = 4″ (0.97 pc), a half-mass radius r _hm = 12″ (2.9 pc), and a concentration parameter c ∼ 1.3 corresponding to a truncation radius r _t ∼ 81″ (19.5 pc). We also derived its integrated absolute magnitude ( M _V = −0.71) and total mass ( M ∼ 80–160 M _⊙ ). The most intriguing feature emerging from this analysis is that KMK 88-10 presents a structure elongated in the direction of NGC 1835, with an intracluster overdensity that suggests the presence of a tidal bridge between the two systems. If confirmed, this would be the first evidence of a tidal capture of a small star cluster by a massive globular.